2018
DOI: 10.1002/cphc.201800259
|View full text |Cite
|
Sign up to set email alerts
|

TCNQ Physisorption on the Topological Insulator Bi2Se3

Abstract: Topological insulators are promising candidates for spintronic applications due to their topologically protected, spin-momentum locked and gapless surface states. The breaking of the time-reversal symmetry after the introduction of magnetic impurities, such as 3d transition metal atoms embedded in two-dimensional molecular networks, could lead to several phenomena interesting for device fabrication. The first step towards the fabrication of metal-organic coordination networks on the surface of a topological in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…Understanding the atom–surface interaction on topological insulators is interesting from a fundamental point of view and may help to obtain a deeper understanding of the interaction with gases and molecules in the physisorption regime. 17,18 For example, as shown recently, the long-range part of the potential can be responsible for band bending effects upon adsorption. 19…”
Section: Introductionmentioning
confidence: 93%
“…Understanding the atom–surface interaction on topological insulators is interesting from a fundamental point of view and may help to obtain a deeper understanding of the interaction with gases and molecules in the physisorption regime. 17,18 For example, as shown recently, the long-range part of the potential can be responsible for band bending effects upon adsorption. 19…”
Section: Introductionmentioning
confidence: 93%
“…18 Intramolecular resolution of individual TCNQ molecules shows a characteristic four-arm pattern composed of two symmetric Ulike protrusions and two bulges centered on the dicyanomethylene groups, separated by a central nodal plane, that resembles the lowest unoccupied molecule orbital (LUMO) of free-standing molecules. 19,20 The observation of negative differential resistance (NDR), i.e., the dip below zero in the STS spectrum (Figure 1c), that is characteristic for molecules weakly adsorbed on supporting substrates, further indicates that the electronic structures of TCNQ molecules are wellpreserved on HOPG. 21−23 Nevertheless, the lack of strong chemical interaction does not preclude interfacial charge transfer.…”
mentioning
confidence: 92%
“…These experimental results contradict one another. The interface between TCNQ, a typical electron acceptor, and Bi 2 Se 3 was studied by Pia et al [5] They observed a DP shift to a higher binding energy by ARPES and a shift of the Bi 4 f core-level toward a lower binding energy accompanied by TCNQ deposition by XPS measurements. These results indicate a chemical interaction between the adsorbed TCNQ and Bi 2 Se 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have been conducted on TI interfaces with organic molecules for use in TIs in spintronic devices. [3][4][5][6][7][8][9] Caputo et al examined the cobalt phthalocyanine (CoPc)/Bi 2 Se 3 interface [4] and observed a slight shift in the Dirac point (DP) to a higher binding energy by angle-resolved photoemission spectroscopy (ARPES) experiments, indicating charge transfer from CoPc to Bi 2 Se 3 . This indicates that the CoPc/Bi 2 Se 3 interface is a weak chemisorption system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation